Response-predictive gene expression profiling of glioma progenitor cells in vitro - Moeckel, Sylvia; Meyer, Katharina; Leukel, Petra; Heudorfer, Fabian; Seliger, Corinna; Stangl, Christina; Bogdahn, Ulrich; Proescholdt, Martin; Brawanski, Alexander; Vollmann-Zwerenz, Arabel; Riemenschneider, Markus J.; Spang, Rainer; et al. (PLoS ONE, 2014)
Background: High-grade gliomas are amongst the most deadly human tumors. Treatment results are disappointing. Still, In several trials around 20% of patients respond to therapy. To date, diagnostic strategies to identify patients that will profit from a specific therapy do not exist. Copyright:
CRIS-Team Scopus Importer:2022-08-05